Pay it forward - Leder, Mimi, 1952-; Spacey, Kevin; Hunt, Helen, 1963-; Osment, Haley Joel, 1988-; Mohr, Jay; Caviezel, Jim, 1968-; Bon Jovi, Jon; Dickinson, Angie; Hyde, Catherine Ryan. (2000)
When a young man starts "paying it forward" for a social studies project, unusual things happen in this bittersweet and uplifting tale
Based on the novel by Catherine Ryan Hyde
"It has been formatted to fit your TV."
PG-13
"18877."
Music by Thomas Newman ; screenplay by Leslie Dixon ; directed by mimi Leder
Kevin Spacey, Helen Hunt, Haley Joel Osment, Jay Mohr, James Caviezel, Jon Bon Jovi, Angie Dickinson
Keywords: Video recordings for the hearing impaired; Videocassettes